The potential impact of the Singapore-Malaysia high speed rail operation on the passenger demand for the low-cost carriers - Ong, Tuan Hock (2018)
The aim of this paper is to forecast the passenger demand and market share of the Low-Cost Carriers (LCC) when the High-Speed Rail (HSR) commence operation in 2026 along the 350 km long Kuala Lumpur-Singapore (KL-SG) route with the possibility that the two-different transport mode will complement with each other. Multinomial Logit model (MNLM) has been developed in order to identify passenger demand which depend on several factors such as en-route travel time, price/fare, frequency, distance and social and economic characteristics of passengers. Stated preference survey has been carried out for the HSR stations: Kuala Lumpur to Singapore. MNLM 2 has been calibrated as per the gathered data from the survey. Sensitivity analysis has been conducted to examine the market potential of the HSR. It has been discovered: (i) travelers turn out to be less sensitive to the frequency of the HSR(ii) the fare price is the significant aspect influencing the HSR market share and thus decreasing LCC market share(iii) LCC and HSR might engage in a robust competition to attain the majority in the corridor.